Influence of oral vitamin E therapy on micro-inflammation and cardiovascular disease markers in chronic hemodialysis patients - Hodková, Magdaléna; Sulková, Sylvie; Kalousová, Marta; Soukupová, Jiřina; Zima, Tomáš; Miková, Dana; Matouš-Malbohan, Ivan; Bartůňková, Jiřina (Renal failure, 2006)
BACKGROUND: The aim of this study was to evaluate the influence of oral vitamin E therapy on serum concentrations of several markers of micro-inflammation and cardiovascular disease in chronic hemodialysis (HD) patients. METHODS: 29 HD patients were randomized into two groups: 15 patients were treated orally with 400 mg of vitamin E daily for a period of five weeks, and 14 patients received no antioxidant supplementation. Before and after vitamin E therapy, serum concentrations of vitamin E (high-performance liquid chromatography), pregnancy-associated plasma protein-A (immunochemical--TRACE assay), C-reactive protein (nephelometry), intercellular adhesion molecule-1 (ELISA), and E-selectin (ELISA) were measured. HD patients were compared with 16 healthy controls. RESULTS: Baseline serum concentrations of PAPP-A and CRP were significantly higher in HD patients than in healthy controls (PAPP-A: 26.23+/-11.94 vs. 11.41+/-1.94 mIU/L, p<0.001; CRP: 5.20+/-3.50 vs. 3.40+/-3.80 mg/L, p<0.05). After five weeks of oral vitamin E intake, serum PAPP-A, CRP, ICAM-1, and E-selectin concentrations remained unchanged in both groups of HD patients. CONCLUSION: Chronic micro-inflammation in HD patients is documented by the elevation of CRP and PAPP-A. A daily oral dose of 400 mg of vitamin E does not seem to be able to reduce enhanced oxidative stress and micro-inflammation in chronic HD patients.
Keywords: financování organizované; Pregnancy-Associated Plasma Protein-A; zánět; Female; Renal Dialysis; chronické selhání ledvin; Intercellular Adhesion Molecule-1; biologické markery; C-Reactive Protein; dialýza ledvin; Biomarkers; ženské pohlaví; vitamin E; E-Selectin; E-selektin; Vitamin E; lidé; Kidney Failure, Chronic; Inflammation; Financing, Organized; Middle Aged; Male; Cardiovascular Diseases; aplikace orální; mezibuněčná adhezivní molekula-1; kardiovaskulární nemoci; lidé středního věku; C-reaktivní protein; Administration, Oral; mužské pohlaví; těhotenský plazmatický protein A; Humans